The Relationship between Inflation, Exchange Rate, Money Supply and Economic Growth in The Gambia - Jawo, Amadou; Jebou, Mohammed; Bayo, Lamin Fatou (Technium Social Sciences Journal, 2023)
Instability in the movement of prices is a major concern in all countries. The rise in foreign exchange and prices of goods and services are among the key factors that causes fluctuation in the economic growth of a country. Thus, this paper adopted the ARDL model to examine whether real effective exchange rate, economic growth and money supply causes Inflation in the Gambia for the period 1985 to 2021. The finding reveals that all our variables causes inflation positively and negatively in the long run and short run respectively at a significant level of 1% except real effective exchange rate and money supply which is significant at 5% level in the long run. The recursive cumulative sum shows that the relationship was stable and the square recursive cumulative sum reveals instability in the relationship of our dependent and independent variables which could be as a result of exogenous shock in output and increase amount of public debts. The study recommends the Gambian government to be caution in taking increase amount of public debts and also the central bank of the Gambia to move from monetary targeting to inflation targeting so as to maintain economic growth and price stability. However, the central bank of the Gambia should assess the entire economy before implementing the policy.